The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3892/ijmm.2020.4628
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNAs are novel players in oral inflammatory disorders, potentially premalignant oral epithelial lesions and oral squamous cell carcinoma (Review)

Abstract: In recent years, a large number of studies have shown that the abnormal expression of long non-coding (lnc)RNAs can lead to a variety of different diseases, including inflammatory disorders, cardiovascular disease, nervous system diseases, and cancers. Recent research has demonstrated the biological characteristics of lncRNAs and the important functions of lncRNAs in oral inflammation, precancerous lesions and cancers. The present review aims to explore and discuss the potential roles of candidate lncRNAs in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…However, the scarcity in the literature studying lncRNAs in OLP was noticed. Accordingly, the review encouraged researchers to further investigate lncRNAs in these disorders to unveil their role [ 36 ]. At the best of the authors’ knowledge, there is only one study investigating the expression of DQ786243 in OLP [ 24 ], concluding that the expression of DQ786243 was significantly upregulated in the CD4+ cells from the peripheral blood of OLP patients compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, the scarcity in the literature studying lncRNAs in OLP was noticed. Accordingly, the review encouraged researchers to further investigate lncRNAs in these disorders to unveil their role [ 36 ]. At the best of the authors’ knowledge, there is only one study investigating the expression of DQ786243 in OLP [ 24 ], concluding that the expression of DQ786243 was significantly upregulated in the CD4+ cells from the peripheral blood of OLP patients compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…The expression and abundance of lncRNAs is tissue specific; they have specific cellular localization, and have the ability to alter signaling pathways by interacting with nucleic acids and proteins. They are involved in gene expression regulation at the pre-, post-, and transcriptional level via changes in the chromatin state, and transcriptional activity, splicing, and translation [ 11 , 12 ]. LncRNAs can be subclassified into the groups of very long intergenic RNAs longer than 10 kb, and macroRNAs, which are pathway specific [ 13 ].…”
Section: Non-coding Rna Transcriptomementioning
confidence: 99%
“…Noncoding RNA (ncRNA), accounting for 90% of the human transcriptome, has been revealed to play a pivotal role in various biological processes via interference with gene expression [ 8 , 9 ]. Emerging evidence has shown that the dysregulated expression of ncRNAs is associated with numerous diseases [ 10 , 11 ]. lncRNAs with a length of more than 200 nucleotides were initially regarded as “transcriptional noise” and nonfunctional [ 12 ].…”
Section: Introductionmentioning
confidence: 99%